IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TERHADAP KEDUDUKAN ANAK LUAR KAWIN - Indra Lesmana; Emilda Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Decision of the Constitutional Court Number 46/PUU-VIII/2010 is considered to have an influenceon the position of children outside of marriage as a follow-up to the non-issuance of the GovernmentRegulation which regulates the position of children outside marriage as mandated by Article 43 paragraph(2) of Law Number 1 of 1974 Based on rational justice, the Constitutional Court then changed the sound ofArticle 43 of Law Number 1 of 1974 to